c - Snellius, Willebrord, 1580-1626; Rothmann, Christoph, active 16th century ([Netherlands] : Elsevier, 2014)
Willebrord Snellius or Willebrord Snel van Royen (1580-1626) was born the son of Leiden University's mathematics professor, and succeeded his father in 1613. Best known in the English-speaking world as Snell, his name was attached to the law of refraction of light. In this title, Snell described a comet that had landed on Earth in November 1618, and includes descriptions of other comets. Through speculations and tables, Snell attempted to follow the comet's course, but other than most scholars in his time, he argued for a physical rather than a spiritual explanation.
'First published by Bonaventura and Mathjis Elzevier in 1619. Republished by Elsevier B.V. in 2014.'
'Nunc primum Will. Sn. R.F. in lucem edita.'
Online resource; title from PDF title page (ScienceDirect, viewed March 30, 2015).
Elsevier
Keywords: Comets -- Early works to 1800.; Comets -- Collisions with Earth -- Early works to 1800.; Comets; Comets -- Collisions with Earth; Electronic books; Early works